2018
DOI: 10.3121/cmr.2018.1389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Near-Infrared Light Therapy Based on Acupoints on the Severity of Restless Legs Syndrome in Patients Undergoing Hemodialysis: A Single-Blind, Randomized Controlled Trial

Abstract: The present study showed that the application of NIR light to acupoints in the legs and feet was as an effective treatment for attenuating the symptoms of RLS in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In a single-blind, randomized controlled trial, 60 hemodialysis patients with RLS received 12 sessions of near infrared (940 nm) treatment to acupoints in the lower limb 3 times a week. In this study, clinically significant improvement was observed, but upon discontinuation the effect was diminished (35). Describing 2 cases with RLS who were treated with acupuncture, Fukutome (36) reported that 4W-acuinjection in Zulinqi (GB41), Kunlun (BL60), Zusanli (ST36), and Sanyinjiao (SP6) acupoints led to immediate relief in the form of a calm sensation and cessation of involuntary movements in legs.…”
Section: Ying Deficiency and Yang Stagnation Leads To Symptomsmentioning
confidence: 65%
“…In a single-blind, randomized controlled trial, 60 hemodialysis patients with RLS received 12 sessions of near infrared (940 nm) treatment to acupoints in the lower limb 3 times a week. In this study, clinically significant improvement was observed, but upon discontinuation the effect was diminished (35). Describing 2 cases with RLS who were treated with acupuncture, Fukutome (36) reported that 4W-acuinjection in Zulinqi (GB41), Kunlun (BL60), Zusanli (ST36), and Sanyinjiao (SP6) acupoints led to immediate relief in the form of a calm sensation and cessation of involuntary movements in legs.…”
Section: Ying Deficiency and Yang Stagnation Leads To Symptomsmentioning
confidence: 65%
“…Non-pharmacologic treatment by pneumatic-compression devices or near-infrared light therapy can improve microvascular circulation during the night to relieve RLS symptoms (58,84,85). Standard acupuncture may be another safe alternative treatment (86).…”
Section: Treatmentmentioning
confidence: 99%
“…Song et al conducted a metanalysis on the effect of exercise on RLS, fatigue, depression and sleeping quality in hemodialysis patients, and he reported that exercise can be effective in improving symptoms of RLS (P < 0.001), fatigue (P < 0.001) and depression (P < 0.001) [ 36 ]. Mohammadi et al performed a single-blind, randomized controlled trial, and he found that near-infrared light can decrease symptoms of RLS in hemodialysis patients [ 37 ]. Kahvecioglu et al declared that there is an improvement of RLS in hemodialysis patients after renal transplantation and normalization of the kidney functions [ 38 ].…”
Section: Reviewmentioning
confidence: 99%